20-6s=

Simple and best practice solution for 20-6s= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 20-6s= equation:


Simplifying
20 + -6s = 0

Solving
20 + -6s = 0

Solving for variable 's'.

Move all terms containing s to the left, all other terms to the right.

Add '-20' to each side of the equation.
20 + -20 + -6s = 0 + -20

Combine like terms: 20 + -20 = 0
0 + -6s = 0 + -20
-6s = 0 + -20

Combine like terms: 0 + -20 = -20
-6s = -20

Divide each side by '-6'.
s = 3.333333333

Simplifying
s = 3.333333333

See similar equations:

| 15(250)+20x=4430 | | 4y+5=y | | 2x-5=30-5x | | 28=3+5x | | 2x(2x)=13x+1 | | 3-(2n-14)+10(n-3)= | | =3x^2+2x-15 | | n*4=45 | | 2x^2-20x=78 | | 264+26s= | | 5x+18=3x+20 | | n+37=52 | | (x-6)=-8x-7 | | 4c^2+1773.8c-151666.67=0 | | n+37+52= | | -2x+3x=3x+2 | | 18.17=3g+3.53 | | 5/4x=-1 | | t/9=7/11 | | 5a+9-(2a-3)=4(a-6)+5a-1 | | 2ln(1-x)=ln(x+5) | | =15x^2-7 | | (x+4)(x+2)(x+3-6i)(x-3-6i)=0 | | 17/y=17 | | (x+3)=2x-18 | | 89y=22(4y+12) | | 3x(3x)-7x-5=0 | | 5/3=-9m | | 2(cosx)(sinx)=0 | | -5(r+2)=-63 | | 3*15+9*15=x | | (8x+15)-(3x+7)= |

Equations solver categories